Ptolemy's science of the stars in the Middle Ages - Juste, David; Dalen, Benno van 1962-; Burnett, Charles 1951-; Hasse, Dag Nikolaus 1969- (Brepols, 2020)
Claudius Ptolemy (c. 100-170 ad) is one of the most influential scholars of all time. While he is also the author of treatises on geography, optics and harmonics, his fame primarily stems from two works on the science of the stars, dealing with mathematical astronomy (the Almagest) and astrology (the Tetrabiblos). The Almagest and the Tetrabiblos remained the fundamental texts on the science of the stars for some 1500 years. Both were translated several times into Arabic and Latin and were heavily commented upon, glossed, discussed, and also criticised and improved upon, in the Islamic world and in Christian Europe. Yet, the reception of Ptolemy in medieval cultures is still to a large extent a terra incognita of the history of science. The Arabic and Latin versions of the Almagest and the Tetrabiblos are for the most part unavailable in modern editions, their manuscripts remain largely unexplored and, generally speaking, their history has never been systematically investigated. This volume gathers together fifteen contributions dealing with various aspects of the reception of Ptolemy’s astronomy and astrology in the Islamic world and in Christian Europe up to the seventeenth century. Contributions are by José Bellver, Jean-Patrice Boudet, Josep Casulleras, Bojidar Dimitrov, Dirk Grupe, Paul Hullmeine, Alexander Jones, Richard L. Kremer, Y. Tzvi Langermann, H. Darrel Rutkin, Michael H. Shank, Nathan Sidoli, Carlos Steel, Johannes Thomann and Henry Zepeda.
Keywords: Ptolemaeus, Claudius -- 100-178; Geschichte 100-1700; Astronomie; Konferenzschrift